Penguatan Bank Perekonomian Rakyat Berbasis Asas Demokrasi Ekonomi: Paradigma Keadilan Sosial - Diaz, Marchethy Riwani (Fakultas Hukum Universitas Surabaya, 2023)
The increasingly complex and numerous fundamental problems in the financial sector are driving financial sector have encouraged reform of the financial industry through the omnibus law, Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector (UUP2SK). The main aim of the presence of UUP2SK is to improve and direct the financial sector to be able to face global dynamics, be fair, sustainable, stable and inclusive as an embodiment of economic democracy which ultimately leads to the creation of social justice. One way of strengthening the financial services sector is through expanding the business activities of People’s Economic Banks (BPR) in Article 13 paragraph (1) letter g UUP2SK which opens up opportunities for BPR’s to collaborate with other financial service institutions, one of which is fintech lending so that they can expand accessibility all levels of society regarding funding. Based on this, the aim of this writing is to find out the implications of the UUP2SK omnibus law on expanding BPR businesses and strengthening BPR based on economic democracy after UUP2SK in realizing social justice for society. This research is normative legal research using a statutory regulatory approach and a conseptual approach. The data used is secondary data through literature study of primary, secondary and tertiary legal materials. The results of this research show that expanding BPR cooperation with other financial service institutions, namely fintech lending, can be a solution for equalizing BPR in Indonesia, as a concretization of the principles of economic democracy in realizing social justice for all society. However, it is necessary to strengthen and improve the level of substance, structure, and legal culture by prioritizing the spirit of economic democracy to realize social justice for the entire community.